The Implementation Of Plan-Do-Check-Act Cycle To Improve The Production Line Productivity In Surface Mounted Technology Area Of Industry - Lee, Hui Xin (Universiti Sains Malaysia, 2019)
Lean has a very extensive collection of tools and concepts. In order to improve the manufacturing operations, one way for an organisation to start, is to use a lean tool that captures their interest and resonates with them in some way. Different organisations may use different techniques to improve their manufacturing process or management. The current project addresses the line productivity improvement of a Surface-MountedTechnology (SMT) by making use of the Lean Tool which is Plan-Do-Check-Act (PDCA) is an iterative methodology that applies a scientific approach to develop a hypothesis, run experiment, evaluate results and refine the experiment. The aim of this project is to improve the production productivity performance of the SMT production line No-6 by the implementation of PDCA and Witness Simulation. It involves problem identification at the SMT production line that has low productivity output due to the problem of high and inconsistent cycle time and provide solution to improve the efficiency of the current situation. There are bottlenecks on certain processes and this situation decelerates the production speed and affects the overall process flow. Therefore, the PDCA methodology is used to serve as a guideline for identifying the root cause of the selected problem, developing and refining countermeasures and implementing finalise solutions. From this research, total of five improvement have been suggested to decrease the cycle time of production processes, so that the actual production unit-per-hour (UPH) can be increased. With the implementation of the PDCA approach as a solution, the line productivity increased and the actual production UPH produced in the SMT production line No-6 increased by 39% (73 units to 102 units) and this helped the company to meet the customer demand.